Proactive scheduling for situated displays - Ribeiro, Fernando Reinaldo (2011)
Public situated displays can represent an important mechanism to enhance users’ experiences and reflect the information and the interactions associated with their environment and the people on it. However, this type of embodiment requires the display system to be able to perform unassisted scheduling based on the current state of the environment in which it is integrated. In this paper, we explore this problem domain and the various ways in which it can be approached. This analysis is organised around three main parts of this problem: which dynamic information to consider, how to introduce domain knowledge for enabling rational choices and how to model the scheduling process itself. We also describe our own approach to these issues, a context-sensitive MAUT scheduler that selects the next item to be presented by determining the one with the highest utility considering the current context of the display.